2014
DOI: 10.1504/ijtp.2014.063105
|View full text |Cite
|
Sign up to set email alerts
|

Demand for tourism in Greece: a panel data analysis using the gravity model

Abstract: Tourism is one of the major drivers of the Greek economy. The contribution of tourism to the Greek economy has proved especially relevant during the period of the credit and euro crises with a high budgetary and balance of payment deficits. From that perspective, this study examines the impact of the socio-economic and geographical determinants of foreign tourism demand in Greece. For the empirical analysis, a panel dataset of 31 countries is used over the period [2001][2002][2003][2004][2005][2006][2007][2008… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
1
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 42 publications
(57 reference statements)
3
27
1
2
Order By: Relevance
“…Habibi () argued that government should integrate hotel development in tourism planning and provide sufficient incentives for the private sector to invest in hotels and its services. In the investigation of demand for tourism in Greece, Chasapopoulos, den Butter, and Mihaylov () argued that sufficient provision of infrastructure and tourism facilities influences tourists' holiday destination choice. They used the statistics on gross investment spending in infrastructure as a proxy and found the estimated coefficient to be insignificant.…”
Section: Introductionmentioning
confidence: 99%
“…Habibi () argued that government should integrate hotel development in tourism planning and provide sufficient incentives for the private sector to invest in hotels and its services. In the investigation of demand for tourism in Greece, Chasapopoulos, den Butter, and Mihaylov () argued that sufficient provision of infrastructure and tourism facilities influences tourists' holiday destination choice. They used the statistics on gross investment spending in infrastructure as a proxy and found the estimated coefficient to be insignificant.…”
Section: Introductionmentioning
confidence: 99%
“…Crampon [21] firstly proposed the tourism gravity model based on Newton's law of gravitation, and held the opinion that tourism for a place depends on the population size and wealth of the tourism-generating region, the attraction of the destination, and the distance between the tourism-generating region and the destination. Scholars also support this opinion in their study of tourism demand [22,23], destination accessibility [16], and distance decay [24], and eastern European countries' potential trade [25]. The tourism gravity model is a typical paradigm to study distance decay in tourism and to analyze the corresponding influence factors.…”
Section: Discussionmentioning
confidence: 93%
“…Mariyono (2017) utilized a dummy to explain the importance of providing policies that guarantee security for tourists. Chasapopoulos et al (2014) stated that Greek policy to become an Olympic event was not favorable for tourism. Kareem (2008) found that democratic political instability impeded tourist visits to Africa.…”
Section: The Findings On Data Panel Analysis Of Previous Researchmentioning
confidence: 99%
“…The general model in this study will follow the empirical model of (Proenca & Soukiazis, 2005;Kareem, 2008;Allen & Yap, 2009;Chasapopoulos et al, 2014;Mariyono, 2017) which identified tourism arrivals or tourist expenditures, income effects, relative prices and infrastructure. They have studied travel requests using the data panel.…”
Section: Demand Estimation Modelmentioning
confidence: 99%